A rare case report: retroperitoneal dedifferentiated liposarcoma associated with paraneoplastic pemphigus - Yang, Fan; Chen, Yangju; Liu, Jiaqing; Gu, Tingyu; Song, Queping; Zhou, Xiao; Xie, Fuan; Gao, Han; Wang, Xueling; Zhang, Qin; Xia, Xiaogang; Wang, Qing; et al. (Frontiers in Surgery, 2025)
BackgroundDedifferentiated liposarcoma (DDLPS) is a rare and aggressive malignant tumor, particularly when occurring in the retroperitoneum. Paraneoplastic pemphigus (PNP) is an uncommon autoimmune mucocutaneous disorder often associated with neoplasia. The coexistence of retroperitoneal DDLPS and PNP is exceptionally uncommon, with only sporadic cases reported worldwide. We present a case of retroperitoneal DDLPS with concurrent PNP in a young male, emphasizing diagnostic challenges and management strategies.Case presentationA 24-year-old male presented with a one-year history of refractory oral ulcerations and a four-month history of a retroperitoneal mass. Initial workup at an outside hospital led to a diagnosis of pemphigus vulgaris, and corticosteroid therapy was initiated without significant improvement. CT demonstrated a large retroperitoneal mass encasing the right iliac vessels and inferior vena cava. Preoperative embolization was performed, followed by complete surgical resection, radiofrequency ablation of residual tumor, and right ureteral stent placement. Histopathology confirmed DDLPS with inflammatory infiltration. Postoperatively, this patient's mucocutaneous lesions improved with continued corticosteroids and topical care.ConclusionThis rare presentation underscores the importance of recognizing paraneoplastic autoimmune syndromes as potential indicators of underlying malignancy. Complete tumor resection remains the cornerstone of management, and multidisciplinary care is essential to optimize both oncologic and autoimmune outcomes.